Colonial Suspects : Suspicion, Imperial Rule, and Colonial Society in Interwar French West Africa - Keller, Kathleen A. (Lincoln : University of Nebraska Press, 2018)
A Vietnamese cook, a German journalist, and a Senegalese student-what did they have in common? They were all suspicious persons kept under surveillance by French colonial authorities in West Africa in the 1920s and 1930s. Colonial Suspects looks at the web of surveillance set up by the French government during the twentieth century as France's empire slipped into crisis. As French West Africa and the French Empire more generally underwent fundamental transformations during the interwar years, French colonial authorities pivoted from a stated policy of "assimilation" to that of "association." Surveillance of both colonial subjects and visitors traveling through the colonies increased in scope. The effect of this change in policy was profound: a "culture of suspicion" became deeply ingrained in French West African society. Kathleen Keller notes that the surveillance techniques developed over time by the French included "shadowing, postal control, port police, informants, denunciations, home searches, and gossip." This ad hoc approach to colonial surveillance mostly proved ineffectual, however, and French colonies became transitory spaces where a global cast of characters intermixed and French power remained precarious. Increasingly, French officials-in the colonies and at home-reacted in short-sighted ways as both perceived and real backlash occurred with respect to communism, pan-Africanism, anticolonialism, black radicalism, and pan-Islamism. Focusing primarily on the port city of Dakar (Senegal), Keller unravels the threads of intrigue, rumor, and misdirection that informed this chaotic period of French colonial history.--
"A vigilant surveillance" : creating suspicion in interwar French West Africa -- "Proceed with a discreet surveillance" : the investigation and surveillance of suspects -- Enemies, charlatans, and propagandists : foreigners under surveillance in AOF -- "Powerless with regard to our nationals" : policing Frenchness and redefining the civilizing mission in AOF -- Creating networks : African suspects, radical politics, and colonial repression.
Based on the author's thesis (doctoral)--Rutgers University, 2007.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Anti-imperialist movements -- France -- Colonies -- History; Anti-imperialist movements -- Africa, French-speaking West -- History -- 20th century; Dissenters -- France -- Colonies -- History; Dissenters -- Africa, French-speaking West -- History -- 20th century; Police patrol -- France -- Colonies -- History; Police patrol -- Africa, French-speaking West -- Surveillance operations -- History -- 20th century; Intelligence service -- France -- Colonies -- History; Intelligence service -- Africa, French-speaking West -- History -- 20th century; Africa, French-speaking West -- Politics and government -- 1884-1960.; Anti-impérialisme -- France -- Colonies -- Histoire; Dissidents -- France -- Colonies -- Histoire; Patrouille policière -- France -- Colonies -- Histoire; Service des renseignements -- France -- Colonies -- Histoire; Afrique occidentale francophone -- Politique et gouvernement -- 1884-1960.; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; HISTORY -- Europe -- France; Anti-imperialist movements; Dissenters; Intelligence service; Police patrol -- Surveillance operations; Politics and government; French-speaking Western Africa; France; 1884-1999; History